2020
DOI: 10.1371/journal.pmed.1003297
|View full text |Cite
|
Sign up to set email alerts
|

Mental health problems among female sex workers in low- and middle-income countries: A systematic review and meta-analysis

Abstract: Background The psychological health of female sex workers (FSWs) has emerged as a major public health concern in many low-and middle-income countries (LMICs). Key risk factors include poverty, low education, violence, alcohol and drug use, human immunodeficiency virus (HIV), and stigma and discrimination. This systematic review and meta-analysis aimed to quantify the prevalence of mental health problems among FSWs in LMICs, and to examine associations with common risk factors. Method and findings The review pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
78
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(112 citation statements)
references
References 93 publications
(224 reference statements)
15
78
2
7
Order By: Relevance
“…While interventions exist that focus on integrating culturally sensitive mental health services into Kenyan communities [41][42][43], these services may be failing to reach key vulnerable populations. A recent systematic review and meta-analysis on mental health in FSW in low-and middle-income countries did not find any single intervention that was designed to address mental disorders among FSW [16]. Research in this field is urgently needed in order to provide effective evidencebased mental healthcare to this key population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While interventions exist that focus on integrating culturally sensitive mental health services into Kenyan communities [41][42][43], these services may be failing to reach key vulnerable populations. A recent systematic review and meta-analysis on mental health in FSW in low-and middle-income countries did not find any single intervention that was designed to address mental disorders among FSW [16]. Research in this field is urgently needed in order to provide effective evidencebased mental healthcare to this key population.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, women with a history of intimate partner violence (IPV) reported that they would be more willing to use PrEP compared to women without these experiences [13,14], further underscoring the importance of HIV prevention in at‐risk populations. However, IPV is also associated with depression [15,16] and substance use among FSW [17]. As such, mental health symptomology may contribute to challenges with PrEP adherence, as has been shown with other antiretroviral medication adherence [18‐20].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that almost nine out of every ten (89.7%) FSWs joined sex work because of poverty. It is well known that many FSWs suffer from depression due to poverty [ 5 ]. FSWs who live in poverty are at higher risk of exposure to life stress and need economic empowerment programs.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis revealed the need for more studies on MD among female sex workers (FSWs) in the low- and middle-income countries (LMICs) since MD among FSWs in the LMICs remains understudied [ 5 ]. The same report indicates that the magnitudes of MD among FSWs vary across countries with the highest prevalence being among FSWs in Jamaica [93.3%] and the lowest prevalence being among FSWs in Bangladesh (4.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation